2020
DOI: 10.1186/s12864-020-06784-8
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear and mitochondrial genomes of Frieseomelitta varia – a highly eusocial stingless bee (Meliponini) with a permanently sterile worker caste

Abstract: Background Most of our understanding on the social behavior and genomics of bees and other social insects is centered on the Western honey bee, Apis mellifera. The genus Apis, however, is a highly derived branch comprising less than a dozen species, four of which genomically characterized. In contrast, for the equally highly eusocial, yet taxonomically and biologically more diverse Meliponini, a full genome sequence was so far available for a single Melipona species only. We present here the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 125 publications
(183 reference statements)
4
19
0
Order By: Relevance
“…In addition, the genome was found to be slightly repetitive, and the estimated genome size of the Malaysian stingless bee (H. itama) was discovered to be approximately 272 Mb. This is similar to the size of previously reported genomes of the honey bee (Apis mellifera-236 Mb) [18], bumble bee (Bombus terrestris-249 Mb) [19] and two Neotropical stingless bee species (M. quadrifasciata-256 Mb, F. varia-275 Mb) [15,16]. Based on the draft genome size estimated, subsequent de novo assembly and genome annotation were performed with the sequencing depth of approximately 49X coverage.…”
Section: Genome Size Estimationsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, the genome was found to be slightly repetitive, and the estimated genome size of the Malaysian stingless bee (H. itama) was discovered to be approximately 272 Mb. This is similar to the size of previously reported genomes of the honey bee (Apis mellifera-236 Mb) [18], bumble bee (Bombus terrestris-249 Mb) [19] and two Neotropical stingless bee species (M. quadrifasciata-256 Mb, F. varia-275 Mb) [15,16]. Based on the draft genome size estimated, subsequent de novo assembly and genome annotation were performed with the sequencing depth of approximately 49X coverage.…”
Section: Genome Size Estimationsupporting
confidence: 82%
“…In addition, the data can be useful as a genomic reference to facilitate future studies on sustainable cultivation and conservation of stingless bees. The sequenced H. itama genome is the first report for the Indo-Malayan/Australasian stingless bee group and the fourth in the world after two Neotropical stingless bees, Melipona quadrifasciata and Frieseomelitta varia [15,16], and an Asian species from Taiwan, Lepidotrigona ventralis hoosana (GenBank accession: PRJNA387986), which had been revised as Lepidotrigona hoozana (Strand) Rasmussen [1].…”
Section: Discussionmentioning
confidence: 99%
“…Living in large colonies with one monandrous queen, F. varia workers are completely sterile with heavily modified and non-functional ovaries [ 50 ]. The genome of F. varia has been sequenced and assembled [ 55 ]. Hence, we chose F. varia to construct a high-quality recombination map using SNP markers, benefitting from recent advances in sequencing technology and the large number of haploid sons produced by a single female in this species.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning stingless bees, works on their epigenetics remain limited. Recently, a complete set of genes involved in DNA methylation and in histone post-translational modifications in the genome of Frieseomellita varia was reported 47 . Moreover, in our previous studies, we demonstrated a functional methylation/demethylation system as well as post-translational modifications of histones in the stingless bee Melipona scutellaris .…”
Section: Introductionmentioning
confidence: 99%